CORRELATION BETWEEN SERUM URIC ACID LEVELS AND NON HDL CHOLESTEROL IN TYPE II DIABETES MELLITUS – AN OBSERVATIONAL STUDY - PROF.DR.A. J. MANJULA DEVI,; DR.S.SRIDEVI, (International Journal of Pharma and Bio Sciences, 2014)
Diabetes mellitus is a systemic metabolic disorder characterized by hyperglycaemia resulting from defects in insulin secretion, insulin action, or both. There is insulin resistance and dyslipidemia which results in micro and macrovascular complications of diabetes. Uric acid, the end product of purine catabolism has been identified as one of the risk factors in the development of metabolic syndrome, coronary artery disease and diabetes mellitus.Non HDL levels are shown to be high in diabetics when compared to healthy individuals. The aim of this study is to evaluate the association between non HDL levels and serum uric acid in type 2 diabetic individuals.